Modern and Contemporary Paintings and Sculpture. (Antwerpen : Galerie Ronny Van de Velde, 1987)
Van Anderlecht, Englebert ; Andre, Carl ; Arman ; Arp, Hans (Jean) ; Baselitz, Georg ; Broodthaers, Marcel ; Calder, Alexander ; Christo ; Riverhead (New York) ; Fontana, Lucio ; Hartung, Hans ; Indiana, Robert ; Joostens, Paul ; Judd, Donald ; Kawara, On ; Kienholz, Edward ; LeWitt, Sol ; Magritte, René ; Manzoni, Piero ; Panamarenko ; Ramsden, Mel ; Raysse, Martial ; Schnabel, Julian ; Schoonhoven, Jan ; Tinguely, Jean ; Vercammen, Wout ; Warhol, Andy
boek